DERAJAT INFESTASI Trichodina sp. PADA LELE DUMBO (Clarias gariepinus) DI EMPAT KOLAM PEMBUDIDAYAAN DI KABUPATEN SUMENEP - Rochiman Sasmita; Miarsono Sigit; Adhitya Yoppy Ro Candra; Achmad Rachman Hidayat (VITEK : Bidang Kedokteran Hewan, 2019)
Abstract This research was aimed to find out the prevalence and degree of infection Trichodiniasis on the Dumbo catfish (Clarias gariepinus) in four ponds cultivation of Sumenep Regency, East Java. The total of 200 samples of Dumbo catfish were from four cultivation ponds to be examined in the Parasitology laboratory of the Faculty of Veterinary Medicine, Univercity Wijaya Kusuma Surabaya. The examination was carried out by means of scraping mucus as well as taking the gill Lamella and observed under the microscope with 100x and 400x magnification. The results showed that the highest level of Trichodiniasis prevalence was in the cultivation pool C (64%) With the degree of infection 5.62 individual parasites/fishes including the category of severe infections while in the pond cultivation A (28%) With the degree of infection 1.86 individual parasitic/fish, cultivation pool B (30%) With the degree of infection 2.46 individual parasites/fishes and the cultivation pond D (48%) With an infection degree 3.02 individual parasites/fishes including a category of mild infections. So using Uji-T can be known results of cases of Trichodiniasis that attacked Dumbo catfish (clarias gariepinus) on four pools of cultivation in Sumenep Regency, East Java showed a very noticeable difference.